(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
In America, racism spread around the country especially in the South. Black people were treated offensively. They did not have full rights as the white citizens. Due to these facts, many black writers responded with a set of literary works and used their skills in writing to reflect on their life. Thus, they have reached an artistic level and produced creative works. African American literature involves poetry and slave narratives.